Use of Post-tensioned Concrete Slabs for Sustainable Design of Buildings - Suleymanoglu, Hikmet; Uzel, Almila; Arslan, Guray (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
Post-tensioned concrete design can lead to considerable savings in materials, construction time and future maintenance costs, compared to the conventional reinforced concrete design. Pre-stressing improves the behaviour of concrete in tension. Thus, for the same imposed load, a more slender structure can be designed. Reduced slab depth results in reduced building height and savings in related building components. These savings translate into less material usage which means reduced embodied energy for a structure thus, creating a sustainable solution. In this study, buildings with post-tensioned and conventional reinforced concrete slab systems are compared. Two buildings with the same floor plans are designed using reinforced concrete and post-tensioned slab systems. The span length is chosen as 6.5 m, which is a practical limit for a relatively economical reinforced concrete solution. The buildings are designed as 10, 20 and 40 stories to demonstrate the change in material savings as the number of floors increases. Since post-tensioned slabs can be designed thinner for the same loads and spans, total weight of the structure reduces and this results in smaller columns, lower seismic loads and foundation loads. The results showed that the difference in steel material savings between conventional and post-tensioned solutions increases as the number of floors increases. It is concluded that incorporating post-tensioning into common design practice not only reduces construction costs but also reduces embodied energy by using less material and produces a sustainable structural design.
Keywords: Post-tensioned floors; Sustainable design; Tall buildings; Construction & Building Technology